2020
DOI: 10.1590/1518-8345.3685.3263
|View full text |Cite
|
Sign up to set email alerts
|

VIDA-Nursing v1.0: immersive virtual reality in vacuum blood collection among adults

Abstract: Objective: to develop and validate the first immersive virtual reality simulation addressing vacuum blood collection in adult patients - VIDA-Nursing v1.0. Method: methodological study to validate 14 steps of the vacuum blood collection procedure in adults, designed to develop the immersive virtual reality simulator VIDA-Nursing v1.0. It was assessed by 15 health workers and 15 nursing undergraduate students in terms of visual, interactive, movement simulation reality, teaching and user-friendly aspects. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 43 publications
0
0
0
5
Order By: Relevance
“…Em concordância a isso, estudo com desenho metodológico realizado em Ribeirão Preto, no interior de São Paulo, sobre utilização de simulador de realidade virtual foi considerado ferramenta válida e promissora para ensinar o procedimento de coleta de sangue a vácuo em adultos entre estudantes de graduação em enfermagem 17 . Na Austrália, estudo qualitativo com 142 acadêmicos de enfermagem revela que o uso de vídeos favoreceu a autoavaliação e reflexão crítica sobre habilidades na comunicação com paciente bem como aumentou a confiança dos discentes em interagir com o público 18 .…”
Section: Discussionunclassified
“…Em concordância a isso, estudo com desenho metodológico realizado em Ribeirão Preto, no interior de São Paulo, sobre utilização de simulador de realidade virtual foi considerado ferramenta válida e promissora para ensinar o procedimento de coleta de sangue a vácuo em adultos entre estudantes de graduação em enfermagem 17 . Na Austrália, estudo qualitativo com 142 acadêmicos de enfermagem revela que o uso de vídeos favoreceu a autoavaliação e reflexão crítica sobre habilidades na comunicação com paciente bem como aumentou a confiança dos discentes em interagir com o público 18 .…”
Section: Discussionunclassified
“…The scenarios focused on acute critical care, [21,22,24,[26][27][28] preoperative nursing processes, [30,31] neonatal infection and pediatric care, [29,30,32,33] and single nursing interventions to include urinary catheterization, [23,25] vacuum blood collection, [34] and observation of patients' symptoms. [35] The storyboard was based on evidence, [13,33] clinical situations, [35] and expert experience, [27][28][29][30][31][32]35] and it was constructed in collaboration with researchers, content experts, [26-29, 31-33, 35] educational experts, [26,28] nursing students, [31,34] and information technology specialists. [23,25,29,30,32,34] In some studies, the scenario development process was not reported.…”
Section: Scenarios For Virtual Reality Simulationmentioning
confidence: 99%
“…[35] The storyboard was based on evidence, [13,33] clinical situations, [35] and expert experience, [27][28][29][30][31][32]35] and it was constructed in collaboration with researchers, content experts, [26-29, 31-33, 35] educational experts, [26,28] nursing students, [31,34] and information technology specialists. [23,25,29,30,32,34] In some studies, the scenario development process was not reported. [21,22,24] The VRS lasted between 10 and 45 minutes, with 20 minutes or less in almost half of the studies (n = 9).…”
Section: Scenarios For Virtual Reality Simulationmentioning
confidence: 99%
“…Para os autores Souza-Junior et al (2020), artigo 3, o simulador "VIDA-Enfermagem v1.0" foi projetado para o ensino das etapas do procedimento de coleta de sangue a vácuo no adulto. O estudo foi avaliado por 15 profissionais da saúde e 15 graduandos de enfermagem em relação aos aspectos visual, interativo, realidade de simulação do movimento, pedagógico e esforço de utilização.…”
Section: Categoria Temática: Simulação Virtual Imersivaunclassified
“…Os simuladores podem ser utilizados por graduandos de enfermagem que estão iniciando no estudo da temática, como uma estratégia a ser combinada com os recursos/habilidades já utilizados no ensino da técnica do procedimento. Assim, proporcionando melhor preparo dos estudantes para o desenvolvimento das competências necessárias para o atendimento ao paciente em estágios supervisionados e, posteriormente, na prática profissional (Souza-Junior, et al, 2020), artigo 3.…”
Section: Categoria Temática: Simulação Virtual Imersivaunclassified